Incidence and long‐term risk of de novo malignancies after liver transplantation with implications for prevention and detection. Issue 11 (14th September 2013) - Schrem, Harald; Kurok, Marlene; Kaltenborn, Alexander; Vogel, Arndt; Walter, Ulla; Zachau, Lea; Manns, Michael P.; Klempnauer, Jürgen; Kleine, Moritz
<x xml:space="preserve">Abstract</x> The goal of this study was the characterization of long‐term cancer risks after liver transplantation (LT) with implications for prevention and detection. Site‐specific cancer incidence rates and characteristics were compared retrospectively for 2000 LT patients from a single institution (January 1, 1983 to December 31, 2010) and the general German population with standardized incidence ratios (SIRs); the total follow‐up at December 31, 2011 was 14, 490 person‐years. The cancer incidence rates for the LT recipients were almost twice as high as those for the age‐ and sex‐matched general population (SIR = 1.94, 95% CI = 1.63‐2.31). Significantly increased SIRs were observed for vulvar carcinoma (SIR = 23.80), posttransplant lymphoproliferative disorder/non‐Hodgkin lymphoma (SIR = 10.95), renal cell carcinoma (SIR = 2.65), lung cancer (SIR = 1.85), and colorectal cancer (SIR = 1.41). The mean time between transplantation and diagnosis was 6.8 years. The mean age at the time of diagnosis was significantly lower for the cohort versus the general population with similar malignancies [50 years (both sexes) versus 69 and 68 years (males and females), P ≤ 0.006]. Tumors were diagnosed at more advanced stages, and there was a trend of higher grading, which suggested more aggressive tumor growth. Tumor treatment was performed according to accepted guidelines. Surprisingly, 5‐year survival was slightly better in the study cohort versus the general population for renal cell carcinoma, lung cancer, colorectal cancer, and thyroid cancer. Long‐term immunosuppression with different protocols did not lead to significantly different SIRs, although patients treated with mycophenolate mofetil had the lowest SIR for de novo cancers (1.65, 95% CI = 1.2‐2.4). Alcoholic liver disease (SIR = 2.30) and primary sclerosing cholangitis (SIR = 3.40) as indications for LT were associated with an increased risk of de novo malignancies. In conclusion, risk‐adapted cancer surveillance is proposed. Tumor treatment performed according to accepted guidelines appears adequate. Mycophenolate may lead to lower long‐term risks for de novo cancers. Liver Transpl 19:1252–1261, 2013. © 2013 AASLD.